2002
DOI: 10.1042/bj20020676
|View full text |Cite
|
Sign up to set email alerts
|

S–S bonds are not required for the sonochemical formation of proteinaceous microspheres: the case of streptavidin

Abstract: Proteinaceous microspheres can be prepared using the sonochemical method. However, it is known that these proteins should possess at least one cysteine residue in order to obtain stable microspheres using this method. In the present study, we have produced streptavidin microspheres, using the sonochemical method, from streptavidin, which does not have any cysteine residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 17 publications
4
57
0
Order By: Relevance
“…[38] Two proteins were examined, BSA and a-amylase. The surfactants used in these experiments were SDS (sodium dodecyl sulphate), CTAB (cetyltrimethyl ammonium bromide), Oleic acid, Tween 40, and Tween 80.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
See 2 more Smart Citations
“…[38] Two proteins were examined, BSA and a-amylase. The surfactants used in these experiments were SDS (sodium dodecyl sulphate), CTAB (cetyltrimethyl ammonium bromide), Oleic acid, Tween 40, and Tween 80.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[20] Two other investigations probing the biological activity of PMs were conducted in Gedankens group. [23,24] In the first, avidin microspheres were prepared by using the sonochemical method. It was found that these microspheres can bind biotin, but to a lesser degree than the native protein.…”
Section: Are Proteinaceous Microspheres Biologicallymentioning
confidence: 99%
See 1 more Smart Citation
“…8 Recently, large poly(R,L-glutamic acid) microspheres (∼5 µm) were reported in passing using ultrasound under strongly acidic conditions. 9 From this prior report, it is probable that their microspheres are not core-shell (n.b., at low pH, PG is insoluble at MW > 6000). Contrary to our results here, Gedanken and coworkers 9 were unable to form microspheres by their methods above pH 4.5.…”
mentioning
confidence: 99%
“…For sulfhydryl-free polypeptides (e.g., polyglutamate), hydrogen bonding or ion pairing between carboxylates [13] provided the mechanism for stabilization of oil-filled microparticles. Avivi and Gedanken [14] suggested that hydrophobic interactions in acidic medium are responsible for the fabrication of poly(glutamic acid) and streptavidin microspheres; -SH functional groups are absent in both of these systems.…”
Section: Introductionmentioning
confidence: 99%